Climate change in EFL: Inquiry-based multimodal writing - Sary Silvhiany; Salsabila Nurhaliza; Rita Inderawati; Kuntum Trilestari (Studies in English Language and Education, 2026)
Climate change represents a significant challenge worldwide, and a growing body of research underscores the need for a multidisciplinary approach to climate change education for youth. This article seeks to enhance the curricular understanding and implementation of climate change education within the context of English language teaching. By utilizing a learner-centered and participatory pedagogical approach, we aimed to raise awareness and empower learners to take action for a sustainable future through English language lessons that incorporate climate literacy. This approach entailed a discussion of pedagogical strategies aimed at engaging students in conversations about climate change issues, facilitating their multimodal engagement in understanding these issues, and fostering the development of dispositions related to climate change. The analysis of interviews, field notes, and learning artefacts revealed that a student-driven experience, which included identifying local climate change challenges, creating action plans, and campaigning for a sustainable environment, facilitated the development of awareness and knowledge about climate change. Additionally, it provided opportunities for students to enhance their critical reading and creative writing skills. The integration of climate change education with elements of English literacy demonstrates the feasibility of incorporating climate change education into EFL classrooms as an interdisciplinary approach to climate change mitigation. The results of this study inform the EFL curriculum by integrating climate change education, ensuring its relevance for students as global citizens concerned about the future of the planet.